INNOVATION AND CHALLENGES OF BLOCKCHAIN TECHNOLOGY IN THE DIGITAL ERA : AN ANALYSIS OF ITS EFFECTIVENESS IN SHARIAH FINANCIAL MANAGEMENT - Muthi'atur Rofi'ah; Moch Syahrul Muzammil (Nurul Jadid University, 2025)
The development of blockchain technology has brought significant innovation to the financial sector, including the management of Shariah-compliant finance, by enhancing transparency, security, and efficiency of financial transactions in accordance with Shariah principles. This technology utilizes distributed ledger technology (DLT) and smart contracts to ensure authenticity and fairness in transactions, thereby strengthening trust and accountability within the Shariah financial system. This study aims to analyze the effectiveness of blockchain implementation in Shariah finance and identify various challenges faced in the digital era, such as immature regulations, limited digital infrastructure, and low levels of technological literacy among industry players. The research method includes a literature review of relevant journals and reports, as well as case studies of blockchain implementation in Shariah financial institutions. The findings indicate that blockchain plays a crucial role in increasing trust and transparency, but its success heavily depends on the synergy among regulators, Shariah financial institutions, and other stakeholders to overcome these obstacles. These results emphasize the importance of collaborative and innovative strategies to support the sustainable growth of the Shariah financial system in the digital age.